Life course socioeconomic position and care dependency in later life: a longitudinal multicohort study from 17 countriesResearch in context - Ting Pan; Chenshuang Li; Ying Zhou (EClinicalMedicine)
Summary: Background: Care dependency, inability to perform basic daily tasks without assistance due to functional impairment, increases substantially with accelerated population ageing and becomes a pressing public health concern worldwide. Socioeconomic disadvantage has been shown to be associated with elevated risks of care dependency, but how risks are modified by changes in socioeconomic position remains unclear. From a life course perspective, we investigated the association between socioeconomic mobility across the lifespan and care dependency in later life. Methods: In this longitudinal multicohort study, we pooled data collected between 2000 and 2019 from six prospective cohort studies across 17 countries from the Program on Global Ageing, Health, and Policy. Socioeconomic status (SES) at three different life stages was assessed based on parental education in childhood, participants’ education in early adulthood, and non-housing wealth in middle-late adulthood. Care dependency was measured using activities of daily living (ADLs) and instrumental activities of daily living (IADLs) following WHO recommendations. Ordinal logistic mixed-effect models were applied to investigate associations between socioeconomic inequalities and their mobility across the life course with later-life care dependency. Furthermore, to investigate contributors to inequalities in care dependency, we applied the difference method to estimate the proportion of these inequalities explained by potential risk factors, and quantified the health and economic benefits of targeted interventions using population attributable fractions. Findings: A total of 103,282 individuals were involved in this study, with an average baseline age of 63.29 (SD 10.70) years and a mean follow-up of 8.75 (SD 0.02) years. Low SES at any stage of life was associated with elevated probability, increased severity, and accelerated deterioration of care dependency in later life, with women being particularly vulnerable. For the probability of IADL dependency, socioeconomic differences by parental education persisted and were greatest at ages 75–80 years (18.10%, 95% CI 14.25%–21.95% for women; 10.23%, 5.82%–14.64% for men). Considering the severity of dependency, differences in low ADL dependency reversed in advanced old age, while differences in high ADL dependency widened consistently with age. Differences in high ADL dependency between high and low childhood SES groups increased from 0.66% (0.64%–0.67%) at age 50 to 15.79% (12.19%–19.39%) at age 100. Compared with a stable high SES throughout life, all other SES mobility trajectories were associated with elevated risks of both IADL and ADL dependency. Individuals who experienced a severe SES decline—high in childhood but low in adulthood—showed a more than ten times higher risk (IADL: OR 18.26, 95% CI 12.45–26.79; ADL: 11.95, 8.47–16.88). A lower risk was observed for those who moved from low SES in childhood to high SES in adulthood (IADL: 2.51, 1.00–6.33; ADL: 1.52, 0.62–3.72). Furthermore, out of risk factors ranging from lifestyles, diseases to social connections, lack of social activities was found to be the primary contributor to socioeconomic inequalities in care dependency (explaining up to 66.63%), with corresponding interventions achieving universal health and economic benefits across countries. Interpretation: Changing socioeconomic status over the lifespan was associated with care dependency risk in later life. Promoting equal educational opportunities from an early age to equitably benefit the most socioeconomically disadvantaged could help mitigate care burdens. Encouraging participation in social activities has the potential to reduce socioeconomic differences in care dependency. Funding: National Natural Science Foundation of China.